Overview of the Current State of Flexible Solar Panels and Photovoltaic Materials - Dallaev, Rashid; Pisarenko, Tatiana; Papež, Nikola; Holcman, Vladimír (MDPI, 2023)
The rapid growth and evolution of solar panel technology have been driven by continuous advancements in materials science. This review paper provides a comprehensive overview of the diverse range of materials employed in modern solar panels, elucidating their roles, properties, and contributions to overall performance. The discussion encompasses both traditional crystalline silicon-based panels and emerging thin-film technologies. A detailed examination of photovoltaic materials, including monocrystalline and polycrystalline silicon as well as alternative materials such as cadmium telluride (CdTe), copper indium gallium selenide (CIGS), and emerging perovskite solar cells, is presented. Furthermore, the impact of transparent conductive materials, encapsulation polymers, and antireflective coatings on solar panel efficiency and durability is explored. The review delves into the synergistic interplay between material properties, manufacturing processes, and environmental considerations. Through a comprehensive

The rapid growth and evolution of solar panel technology have been driven by continuous advancements in materials science. This review paper provides a comprehensive overview of the diverse range of materials employed in modern solar panels, elucidating their roles, properties, and contributions to overall performance. The discussion encompasses both traditional crystalline silicon-based panels and emerging thin-film technologies. A detailed examination of photovoltaic materials, including monocrystalline and polycrystalline silicon as well as alternative materials such as cadmium telluride (CdTe), copper indium gallium selenide (CIGS), and emerging perovskite solar cells, is presented. Furthermore, the impact of transparent conductive materials, encapsulation polymers, and antireflective coatings on solar panel efficiency and durability is explored. The review delves into the synergistic interplay between material properties, manufacturing processes, and environmental considerations. Through a comprehensive
Overview of the Current State of Flexible Solar Panels and Photovoltaic Materials
Keywords: solar panels; photovoltaics; perovskite-based; silicon-based; flexible; solar panels; photovoltaics; perovskite-based; silicon-based; flexible